2001
DOI: 10.5694/j.1326-5377.2001.tb143093.x
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and nature of connexin 26 mutations in children with non‐syndromic deafness

Abstract: Objective To determine (1) the prevalence and nature of connexin 26 mutations in a cohort of Australian children with non‐syndromic hearing loss, and (2) the carrier frequency of the common connexin 26 mutation (35delG) in the general population. Design A cohort, case‐finding study. Mutation analysis was performed on DNA extracted from white blood cells, buccal cells, or Guthrie blood spots. Setting A hearing loss investigation clinic and a deafness centre in two Australian capital cities, 1 January 1998 to 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
25
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 18 publications
4
25
0
Order By: Relevance
“…This mutation was previously reported in Australian and Indian populations (Dahl et al 2001; Mani et al 2009) and was shown to impair trafficking of the protein to the plasma membrane. Given the shared ancestral history of Pakistan and India, it is tempting to speculate that p.I35S may be another ancestral mutation in the subcontinent.…”
Section: Discussionsupporting
confidence: 54%
“…This mutation was previously reported in Australian and Indian populations (Dahl et al 2001; Mani et al 2009) and was shown to impair trafficking of the protein to the plasma membrane. Given the shared ancestral history of Pakistan and India, it is tempting to speculate that p.I35S may be another ancestral mutation in the subcontinent.…”
Section: Discussionsupporting
confidence: 54%
“…The pathogenic effect of these single mutations are uncertain, but we have attributed the hearing losses to thise GJB2 gene changes, because the proportion of children with hearing loss and one detectable recessive GJB2 mutation is significantly higher than that of the general population (approximately 1%) [29]. The pathogenic effects of a number of other changes in the GJB2 gene of 24 children are also ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…This is within the expected range, as the 35delG carrier frequency in the Australian population has previously been estimated to be 1:100 and the overall prevalence of carriers of connexin 26 mutations to be 1:50. 10 The V37I amino acid substitution was found as a single change in two cases (one Asian and one ''more than one race''). No other GJB2 or GJB6 mutations were detected in these two children.…”
Section: Discussionmentioning
confidence: 99%
“…Although two biallelic GJB2 mutations were found in 34 of these children, 18 (35%) had a detectable mutation in only one allele. 10 This number is too high to represent carriers of GJB2 mutations with another cause of deafness. Therefore, it was concluded that the GJB2 mutations in many of these 18 children might be associated with the hearing loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation